Impact of waiting times for radiotherapy for cervical cancer - Lohlun, Kim Nicole (My University, 2014)
Radiotherapy plays a vital role in cervical cancer management. However, due to high patient load and limited resources, waiting lists are unacceptably long. This prospective study aimed to evaluate the potential impact of radiotherapy delays. Patients and methods Eighty-one patients requiring radical radiotherapy for cervical cancer were selected. Patients were re-evaluated every four weeks while waiting, and again at simulation. Results Median delay from first consultation to simulation was 55 days. Longer delays were not statistically correlated to tumour progression. Most of the upstaging occurred around 40 to 65 days. One in four patients received blood transfusions and required hospital admission. Four patients needed haemostatic brachytherapy for bleeding. Conclusion A relationship between time waited and disease progression could not be proven. However, numbers were small and statistical tests were likely underpowered. The study does, however, highlight unacceptably long delays for radiotherapy and a wait of less than 40 days is recommended.